Data on tree height and diameter for Pinus kesiya in Zambia - Phillimon Ng'andwe; Donald Chungu; Arthur M. Yambayamba; Alice Chilambwe (Data in Brief, 2019)
Forest inventories in plantations of non-native trees are conducted every five years in Zambia. Characteristics of data collected through these inventories are presented here. The data includes diameter at breast height (d), total tree height (h) and rotation categories for trees sampled. This data supported the development of robust h-d models for planted Pinus kesiya in the country. We have also presented graphical visualization of the composition and trends of the data by site and rotation. Datasets were filtered and cleaned and are ready to be used for other purposes in order to improve understanding of P. kesiya growth. For more insight please see “Modeling the height-diameter relationship of planted Pinus kesiya in Zambia” (Ng’andwe et al., 2019). Keywords: Rotation, Pine trees, H-d model, Data